First Record of Free-Living Nematode Ironus dentifurcatus Argo & Heyns, 1972 (Ironidae: Enoplida) From Indonesia - Pradana, Ankardiansyah Pandu; Yoshiga, Toyoshi (Universitas Negeri Semarang, 2025)
Free-living nematodes often serve as the bioindicators of environmental quality. These nematodes are highly sensitive to even minute changes in the environment. Studies related to the presence of free-living nematodes have flourished, but to date, only a few studies have investigated the morphological and molecular characterization of free-living nematodes from agroecosystems in Indonesia. This study aimed to characterize the free-living nematode Ironus spp. from the rhizosphere of Arabica coffee plants in Bondowoso Regency, Indonesia. Nematodes were extracted from the soil using the white-head tray method and then preserved in a DESS solution to maintain their morphology and DNA. The morphometric analysis of Ironus species obtained in this study showed that the nematode species is identical to Ironus dentifurcatus. The small subunit (SSU) region of rDNA of the nematode was successfully amplified using primers (SSU F07 and SSU R 81). The results of phylogenetic analysis and sequence homology showed that the sequence in this study showed up to 95% homology to Ironus spp. In the database. This is the first study documenting I. dentifurcatus in Indonesia that integrates morphological and molecular characterization.